Beak-trimming methods and their effect on the performance of japanese quail pullets (Coturnix japonica) - Pizzolante, CC; Garcia, Edivaldo Antonio [UNESP]; Saldanha, EAPB; Laganá, C; Batista, L [UNESP]; Deodato, Ap; Souza, ALP (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
This study aimed at verifying if beak-trimming methods in Japanese quail pullets could optimize production by decreasing stress caused by cannibalism. A total number of 816 day-old Japanese quails was distributed in a completely randomized experimental design in a 2 x 3 factorial arrangement, with two beak-trimming ages (14 and 21 days of age) and three beak-trimming sizes (not trimmed, 1/3 trimmed, or 1/2 trimmed), and 4 replicates of 34 birds per replicate. Birds were submitted to the same management and feeding conditions. Weight gain, feed intake, feed conversion ratio, and mortality were evaluated. There was no significant effect of age at beak trimming on the evaluated parameters (P>0.05), as well as no significant interaction between age at beak trimming, and beak-trimming method. There was a significant effect (P<0.01) of trimming size on performance, with the best performance observed in birds not submitted to beak trimming or had 1/2 of the beak trimmed. When the beak was more aggressively trimmed (1/2), parameters were worse. According to the obtained results, it is recommended to trim 1/3 of the beaks, which can be performed either at 14 or 21 days of age.
Keywords: Japanese quail; beak trimming; performance; pullet phase